(Re)Claiming Our Expertise: Parsing Large Text Corpora With Manually Validated and Organic Dictionaries. (3rd April 2019) - Muddiman, Ashley; McGregor, Shannon C.; Stroud, Natalie Jomini
Abstract : Content analysis of large-scale textual data sets poses myriad problems, particularly when researchers seek to analyze content that is both theoretically derived and context dependent. In this piece, we detail the approach we developed to tackle the analysis of the context-dependent content of political incivility. After describing our manually validated organic dictionaries approach, we compare the method to others we could have used and then replicate the method in a different—but still context-dependent—project examining political issue content on social media. We conclude by summarizing the strengths and weaknesses of the approach and offering suggestions for future research that can refine and expand the method.